2019
DOI: 10.4149/neo_2018_180829n656
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG20 promotes tumorigenesis and cancer stemness in glioblastoma via activating PI3K/Akt/mTOR signaling pathway

Abstract: Long noncoding RNAs (lncRNAs) play crucial roles in the development of human cancers. LncRNA small nucleolar RNA host gene 20 (SNHG20) has been reported to be an oncogene in several cancers, whereas the specific role of SNHG20 in glioblastoma is unclear. In this study, we found that SNHG20 was significantly upregulated in glioblastoma tissues and cell lines. Survival analysis suggested that high expression of SNHG20 indicated the low overall survival rate of glioblastoma patients. Subsequently, gain or loss-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…Additionally, SNHG20 could exert its carcinogenic action in breast cancer, and high level of SNHG20 could facilitate the proliferation, invasion and metastasis of cancer cells via modulating miR-495/HER2 axis [30]. Meanwhile, SNHG20 also elevated tumor progression by controlling the epithelial-to-mesenchymal transition (EMT) signaling pathway in osteosarcoma or hepatocellular carcinoma [23,24,31], activating PI3K/Akt/mTOR pathway in glioblastoma [25], as well as upregulating the expression of transforming growth factor-β1 (TGF-β1) in nasopharyngeal carcinoma [18], etc. Given these above molecular mechanisms of SNHG20 among various carcinomas, it was obvious that SNHG20 was connected with an unfavorable prognosis in cancer patients, which further provided support for clinical utility of SNHG20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SNHG20 could exert its carcinogenic action in breast cancer, and high level of SNHG20 could facilitate the proliferation, invasion and metastasis of cancer cells via modulating miR-495/HER2 axis [30]. Meanwhile, SNHG20 also elevated tumor progression by controlling the epithelial-to-mesenchymal transition (EMT) signaling pathway in osteosarcoma or hepatocellular carcinoma [23,24,31], activating PI3K/Akt/mTOR pathway in glioblastoma [25], as well as upregulating the expression of transforming growth factor-β1 (TGF-β1) in nasopharyngeal carcinoma [18], etc. Given these above molecular mechanisms of SNHG20 among various carcinomas, it was obvious that SNHG20 was connected with an unfavorable prognosis in cancer patients, which further provided support for clinical utility of SNHG20.…”
Section: Discussionmentioning
confidence: 99%
“…These studies containing 1187 cancer patients had an accrual period between 2016 and 2019 and sample sizes varying from 32 to 144 (mean, 79). Each and every research study was performed in China; two studies referred to hepatocellular carcinoma [8,23], two studies involved osteosarcoma [10,24], two studies touched upon glioma [11,25], and the remaining nine studies related to colorectal cancer [12], gastric cancer [13], lung cancer [14], cervical cancer [15], esophageal carcinoma [16], oral carcinoma [17], nasopharyngeal carcinoma [18], ovarian cancer [19], and laryngeal carcinoma [20]. The whole subjects registered were separated into high and low SNHG20 group on the basis of the SNHG20 measurement results.…”
Section: Data Selection and Characteristicsmentioning
confidence: 99%
“…Its overexpression is associated with tumor size, clinical stage, and poor prognosis in patients with hepatocellular carcinoma. Currently, lncRNA SNHG20 has been confirmed as a dysregulated oncogene in other several malignancies, such as gastric cancer [11], glioblastoma [17], NSCLC [18]. Moreover, the silence of SNHG20 significantly suppressed cell proliferation, migration, and invasion in a variety of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that lncRNA SNHG20 could promote the proliferation, migration, and invasion of bladder cancer and ovarian cancer by activating the Wnt/β-catenin signal pathway [27,31]. Moreover, several important pathway was confirmed to be modulated by SNHG20 in various cancers, including GSK-3β/β-catenin signaling pathway in gastric cancer [28], MDM2-p53 pathway and PTEN/PI3K/AKT signaling pathway in glioma [32,33], PI3K/Akt/mTOR signaling pathway in glioblastoma [17], ATM-JAK-PD-L1 pathway in ESCC [25], and MEK/ERK pathway in cervical cancer [34]. Furthermore, SNHG20 could promote vasculogenic mimicry formation of glioma cells by activating FOXK1 [35] and accelerate the proliferation of hepatocellular carcinoma by upregulate HBx and downregulate PTEN [36].…”
Section: Discussionmentioning
confidence: 99%
“…As such, lncRNAs have been shown to play an important role in mediating pluripotency, self-renewal, and differentiation programs in embryonic stem cells (ESC) (Guttman et al 2011;Khalil et al 2009;Wang et al 2013). In addition, lncRNAs have been shown to be important in CSC biology (Mineo et al 2016;Gao et al 2019;Bhan et al 2017;Schmitt and Chang 2016).…”
Section: Introductionmentioning
confidence: 99%